(3aVd UfGYI GdWHs - (3eMeO Hf jhSa Hf YeQ Hf TYjH GdMSfj GdSfhSj , CHh YHO Gddg, J (B895 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HGdbOe cdGe ai aVd UfGYI GdWH , hCfgG TWQ GdYde , dbhdg Ydjg GdUdGI hGdSdGe (B: (3GdYde YdeGf , Yde GdCOjGf hYde GdCHOGf s
(3BNQgG (B:s
(3hcPdc JbHd GdCYVGA bHhdkG MSfkG , hdGSJaQGZgG ef GdaVdGJ HSHH GdQjGVI , aJSJbje HPdc GdUMI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B154 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B132s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B171 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(474 (3c(B) s
Keywords: (3GdWHs